2022
DOI: 10.1016/j.jcmgh.2021.09.012
|View full text |Cite
|
Sign up to set email alerts
|

IL13 Acts Directly on Gastric Epithelial Cells to Promote Metaplasia Development During Chronic Gastritis

Abstract: Interleukin 13 (IL13) is secreted by multiple subsets of immune cells and acts directly on the gastric epithelium to promote neck cell expansion and metaplasia. Mice with autoimmune gastritis lacking the IL13 receptor do not develop neck cell expansion or metaplasia, and neutralization of IL13 inhibits and reverses disease development during chronic gastritis. BACKGROUND & AIMS:It is well established that chronic inflammation promotes gastric cancer-associated metaplasia, but little is known regarding the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 70 publications
1
20
0
Order By: Relevance
“…IL-17 and IFN-γ in this model have been found to induce parietal cell atrophy initiating pathology in the corpus of the stomach (Bockerstett et al, 2018;Osaki et al, 2019). The type two cytokine IL-13 was also found to have a profound impact on progressing gastric pathology beyond atrophic gastritis in TxA23 animals, driving metaplastic transformation in the tissue (Noto et al, 2021). These mice also show significant increases in pSTAT3 and IL-6, two molecules known to be associated with human carcinomas .…”
Section: Autoimmune Gastritismentioning
confidence: 68%
See 1 more Smart Citation
“…IL-17 and IFN-γ in this model have been found to induce parietal cell atrophy initiating pathology in the corpus of the stomach (Bockerstett et al, 2018;Osaki et al, 2019). The type two cytokine IL-13 was also found to have a profound impact on progressing gastric pathology beyond atrophic gastritis in TxA23 animals, driving metaplastic transformation in the tissue (Noto et al, 2021). These mice also show significant increases in pSTAT3 and IL-6, two molecules known to be associated with human carcinomas .…”
Section: Autoimmune Gastritismentioning
confidence: 68%
“…Remarkable similarities include a considerable lymphocytic infiltration with predominant Th1-and Th17-differentiated effectors and inflammation-responding epithelial cells upregulating MHC II molecules to aid in CD4 + T cell activation (Smythies et al, 2000;Shi et al, 2010;Archimandritis et al, 2000;D'Elios et al, 2001;Burman et al, 1992;. While type two cytokines, IL-4 and IL-13, are not responsible for initiating inflammation in response to either Hp or AIG, studies have found them to be critical for promoting severe metaplastic and even dysplastic lesions as disease progresses beyond gastritis (Marotti et al, 2008;Gabitass et al, 2011;Miska et al, 2018;Petersen et al, 2018;De Salvo et al, 2021;Noto et al, 2021). Cells like dendritic cells, macrophages, mast cells, and eosinophils have also been identified in both disease settings (Burman et al, 1992;Nakajima et al, 1997;Ninomiya et al, 2000;Suzuki et al, 2002;Hafsi et al, 2004;Moorchung et al, 2006;Khamri et al, 2010;Park et al, 2013;Bockerstett et al, 2020;Go et al, 2021).…”
Section: Comparison Of Helicobacter Pylori and Autoimmune Gastritismentioning
confidence: 99%
“…This led to the hypothesis that IL-13 is driving M2 recruitment/ polarization in the gastric mucosa. IL-13 is thought to be produced by Th2 cells, but macrophages, mast cells, and ILC2s are also capable of producing IL-13, as observed in mouse models of gastric disease (49)(50)(51). Busada et al ( 2019) used a mouse model where precancerous gastric lesions were induced by eliminating androgen and glucocorticoid signaling, inflicting gastric inflammation and tissue damage (50,80).…”
Section: Mast Cells and Ilc2smentioning
confidence: 99%
“…Future scRNAseq work should compare SPEM arising out of other etiologies of gastritis, including the most common risk factor for gastric cancer, Helicobacter pylori infection (5). Noto et al ( 2021) also found that IL-4 and/or IL-13, produced by mast cells or ILC2s, were required to drive the epithelial cell transition from precursor inflamed epithelial cells toward SPEM (49). Interestingly, in autoimmune animals that lack the IL-4/IL-13 receptors, making both epithelial and immune cells unable to respond to signaling, inflamed precursor epithelial cells arise but fail to progress to SPEM.…”
Section: Epithelial Cell Response To Inflammationmentioning
confidence: 99%
See 1 more Smart Citation